Donor Microbiota Composition and Housing Affect Recapitulation of Obese Phenotypes in a Human Microbiota-Associated Murine Model - Kaiser, Thomas; Nalluri, Harika; Zhu, Zhigang; Staley, Christopher (Frontiers in Cellular and Infection Microbiology, 2021)
Human microbiota-associated (HMA) mouse models offer a valuable approach to study the role of intestinal microbiota in the development of obesity. In this study, we used an HMA model to evaluate whether engraftment of human obese or lean microbiota, from each of three donors, could recapitulate host phenotypes under conventional and specific-pathogen-free housing. Microbiota engraftment was correlated with donor relative abundances of the class Bacteroidia (Spearman’s ρ = 0.73, P ≤ 0.001), and one obese donor resulted in significant weight gain (P ≤ 0.003) and compromised insulin sensitivity under conventional housing. SPF housing partially blunted phenotypic response. Results of this study indicate that our HMA model partially recapitulates obese phenotypes under conventional housing and highlights a need to consider donor-specific effects as well as housing conditions when studying the role of the microbiota in obesity.